Dramatyzacja tradycji. Dramaturgiczne konfrontacje z kanonem literackim - Dobrowolski, Piotr (Przestrzenie Teorii, 2021)
The article opens with a statement that dramaturgical creativity, long marginalized by literary studies, has returned to the area of its interest together with its researchers’ use of the achievements of performative and cultural turns. Taking these into account allows us to treat drama as a distinctive literary practice in which the reception of a text is exemplary. As the author claims, with the New Humanities, integrating scattered reading perspectives known to the history of literary studies into the horizons of New Positivity, dramatic studies enrich this standpoint and maintain a critical view making creative use of the antagonism of perspectives, confrontation of attitudes, conflict of qualities or different visions and ideas. The potential tensions revealed in the practice of active reading of a literary text in accordance with the dramatic matrix guarantee the positive effects of each act of engaged reading. The dramatization of tradition is a specific field of critical dialogue between the reader and the existing literary tradition. Three dramatic works by Jan Czapliński are indicated as examples of mediators for this dialogue. The work of this playwright presents and suggests a critical reading of the characters and works of Gabriela Zapolska, Henryk Sienkiewicz and Adam Mickiewicz, leading to the emancipation of their works that is situated beyond the framework of the discursively created, existing canon of contemporary Polish literature and culture. A critical view enriches and updates the canon. Dramatization, which allows the revaluation of existing values, appears as the basic category of contemporary art – revealing existing, usually ineffable conflicts and using them to build new, positive values.